Sustainable Knowledge, Awareness, Attitude And Intention For Gen-Z Sustainable Consumption - Rubiyanto Rubiyanto; Maria Angela Diva Vilaningrum W; Ima Kristina Yulita; Maria Theresia Ernawati; Trisnawati Rahayu (UNIVED Press, 2024)
Knowledge, awareness, and attitude towards sustainable consumption have an impact on someone to change behavior that is more towards sustainable consumption. This research aims to provide the effect of sustainable knowledge, sustainable awareness, and attitude towards sustainable consumption on intention to sustainable consumption. Data collection techniques using self-administered surveys are self-administered by distributing online questionnaires. The sampling method uses non-probability sampling techniques with purposive sampling. The criteria used in the sampling of this study were Gen-Z who knew sustainable products. The statistical test used in this study to test the data was regression analysis using SPSS 26. In the early stages of testing and data analysis, instrument testing was carried out with validity tests and reliability tests as well as classical assumption tests. Testing of models and hypotheses is done with T-test and T-test. According to this research, sustainable knowledge has no effect on Intention toward sustainable consumption, sustainable awareness affects Intention toward sustainable consumption, and attitude toward sustainable consumption affects intention toward sustainable consumption.